2017
DOI: 10.1016/j.psychres.2017.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Stigma resistance and its association with internalised stigma and psychosocial outcomes among psychiatric outpatients

Abstract: Studies have suggested that stigma resistance plays an important role in the recovery from mental illness. However, there has been limited research in Asian countries that has examined the benefits of stigma resistance among the mentally ill in Asian populations. Hence, this study aimed to assess the prevalence of stigma resistance and establish the socio-demographic correlates of stigma resistance, as well as its association with internalised stigma and psychosocial outcomes among a multi-ethnic population of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 32 publications
4
37
1
Order By: Relevance
“…This study found 49.5% overall percentage score of stigma resistance, and this figure is lower than the study carried out in Europe (59.7%) [21], Singapore (89.2%) [22], and China (76%) [23]. And this variation may be due to the difference in the sociodemographic characteristics of the patients; most of the patients in other study areas have more than a secondary level of education which contributes for better coping with stigma and a good mental health care setting which contributes for better care and treatment outcome.…”
Section: Discussioncontrasting
confidence: 87%
“…This study found 49.5% overall percentage score of stigma resistance, and this figure is lower than the study carried out in Europe (59.7%) [21], Singapore (89.2%) [22], and China (76%) [23]. And this variation may be due to the difference in the sociodemographic characteristics of the patients; most of the patients in other study areas have more than a secondary level of education which contributes for better coping with stigma and a good mental health care setting which contributes for better care and treatment outcome.…”
Section: Discussioncontrasting
confidence: 87%
“…Disorder severity negatively predicted mental health component of health-related quality of life (HRQOL) for Singaporeans suffering from depression [9]. Among Singaporean psychiatric outpatients with depression and anxiety disorders, 43.6% experienced moderate to high levels of self-stigma [93]. For patients with schizophrenia, the number of hospitalizations negatively predicted the mental health component of HRQOL [94].…”
Section: Stigma Related To Psychiatric Illnesses and Advancement Of Amentioning
confidence: 99%
“…Patients with psychiatric conditions frequently experience feelings of stigmatization at higher rates than those without psychiatric conditions (10). In a subgroup analysis, the odds ratio of perceived stigma among patients with psychogenic nonepileptic seizures compared with those with epilepsy was found to be 4.27, suggesting a fourfold greater odds in an individual's lifetime (11).…”
Section: Stigma and Provider Misunderstandingmentioning
confidence: 89%